2018
DOI: 10.1002/elsc.201800045
|View full text |Cite
|
Sign up to set email alerts
|

Identification and molecular docking of novel ACE inhibitory peptides from protein hydrolysates of shrimp waste

Abstract: The effect of enzymatic hydrolysis by Savinase on the interfacial properties and antihypertensive activity of shrimp waste proteins was evaluated. The physicochemical characterization, interfacial tension, and surface characteristics of shrimp waste protein hydrolysates (SWPH) using different enzyme/substrate (E/S) (SWPH5 (SWPH using E/S = 5), SWPH15 (SWPH using E/S = 15), and SWPH40 (SWPH using E/S = 40)) were also studied. SWPH5, SWPH15, and SWPH40 had an isoelectric pH around 2.07, 2.17, and 2.54 respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…Figure 4 shows that lower-molecular-weight Pep have higher IA than PH, in accordance with Krichen et al’s results [ 48 ], which indicated a higher activity in peptide fractions from protein hydrolysates of shrimp waste ( P. longirostris ) than in whole hydrolysates.…”
Section: Resultssupporting
confidence: 88%
“…Figure 4 shows that lower-molecular-weight Pep have higher IA than PH, in accordance with Krichen et al’s results [ 48 ], which indicated a higher activity in peptide fractions from protein hydrolysates of shrimp waste ( P. longirostris ) than in whole hydrolysates.…”
Section: Resultssupporting
confidence: 88%
“…This diversity, together with the availability of marine resources, have driven the search for new antihypertensive agents, which could be administered as functional foods or dietary supplements. Since the first discovery of a marine-derived peptide with ACE-inhibitory activity, researchers have identified a variety of antihypertensive peptides in hydrolysates from marine species, such as Synodus macrops [ 12 ] (AGPPGSDGQPGAK, IC 50 = 0.42 mM), Salmo salar [ 13 ] (GAR and IGPR, IC 50 = 0.598, 0.43 mM), shrimps (SSSKAKKMP, IC 50 = 0.88 mM) [ 14 ], and Ruditapes philippinarum (pRPH, tRPH and nRPH, IC 50 = 0.42, 2.93 and 3.53 mg/mL) [ 15 ]. Some marine-derived peptides are currently being evaluated for safety and efficacy through ongoing clinical trials which have advanced to different phases, and even a small number have entered the market.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally the sequence of these four ACE-inhibitory peptides are Lys-Pro-Ala-Gly-Asp-Phe (Z-I-1), Lys-Ala-Ala-Leu-Ser-Gly-Met (Z-I-2), Lys-Lys-Ala-Ala-Met-Ala-Met (Z-I-3), and Leu-Asp-His-Val-Pro-Gly-Gly-Ala-Arg (Z-I-4). Krichen et al (2018) reported the extraction of four ACE-inhibitory peptides from shrimp and showed that hydrophobic amino acids at the N-terminus might contribute to an increase in the ACE-inhibitory activity of peptides. Here, Leu-Asp-His-Val-Pro-Gly-Gly-Ala-Arg similarly has leucine at the N-terminal end.…”
Section: Resultsmentioning
confidence: 99%
“…ACE plays a critical role in these pathways to maintain blood pressure at a balanced level (Rice et al, 2004; Sanli et al, 2018). The inhibitory activities of ACE are considered to be an effective way to treat hypertension (Krichen et al, 2018). Many synthetic ACE inhibitors, which are used to regulate blood pressure during clinical treatment, present some safety hazards for humans, such as potential induced coughing, renal impairment, and allergic reactions (Alhaj, 2017).…”
Section: Introductionmentioning
confidence: 99%